ANALISIS IMPLEMENTASI PROMOTIONAL MIX DALAM MENINGKATKAN VOLUME PENJUALAN KENDARAAN BERMOTOR (KASUS PADA DEALER MOTOR YAMAHA PT.DASATAMA CEMERLANG MOTORINDO DUMAI) - Dea Pratama Emylia; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Promotional mix is a combination of the best strategy of the variables of advertising , sales promotion , publicity , personal selling all of which are planned to achieve sales program . The sales volume is the end result achieved by the company from the sales generated by the company. PT . Dasatama Cemerlang Motorindo Dumai is a company engaged in the sale , service and spare parts of motorcycles yamaha . In the normal course of business the last few years the company was not able to achieve sales targets and sales volumes decreased . Promotion strategies used are promotional mix such as advertising , sales promotion , publicity , personal selling . The results of this study indicate that the analysis of the implementation of promotional mix effect on the increase in sales volume . Judging from the responses of respondents who chose a variable advertising compared to many other variables that will further optimize the increase in volume of sales at PT . Dasatama Cemerlang Motorindo Dumai .Keyword : (advertising, sales promotion, personal selling, publicity,sales volume